Analysis of Knowledge and Stress Levels of Mothers with Exclusive Breastfeeding - Dedi Saifulah; Endra Widiyanto; Faiqotul Laila; Mifthakhur Rohmah (Journal of Health Science Community, 2023)
Breastfeeding (ASI) for newborns is an effort to prevent death and malnutrition in infants and toddlers. In general, the ideal breastfeeding is given exclusively for the first 6 months of life then continued with complementary foods until the age of 2 years. Some of the benefits of exclusive breastfeeding can prevent postpartum hemorrhage, anemia, and breast carcinoma. This journal search is conducted electronically and online using one database, namely the Google Scholar from 2015-2020 combining the following keywords: Stress with exclusive breastfeeding (Google Scholar), Knowledge with Exclusive Breastfeeding (Google Scholar) The inclusion criteria for journals have the same variables as research, the journals used are journals for the last 5 years which have 30-200 respondents from Indonesia. Based on the journals that have been reviewed, it is found that from the six journals there is a proven relationship between knowledge and stress levels with exclusive breastfeeding. This is evidenced from the results of previous research. So, Mother’s Knowledge and Stress Level influence exclusive breastfeeding. The aim of the researcher on the Analysis of Mother’s Knowledge and Stress Level by giving exclusive breastfeeding is to analyze the mother’s knowledge level, to analyze the mother’s stress level, to analyze the giving of exclusive breastfeeding, to analyze the knowledge and the level of mother’s stress by giving exclusive breastfeeding.